The Pegasus Snooping Case: A Legal Analysis of the National Security VS Individual Privacy Paradigm - Parimala, Veda (Journal of Social Science and Humanities, 2025)
In the Technology Era, conflict between the individual’s identity and legislative regulation is inevitable. Snooping case is one of the glaring examples to defy the citizenry inalienable rights. The Pegasus snooping case has raised several difficult questions in the field of spyware and individual privacy. This is the first and foremost matter of the surveillance at large scale involves a large number of veteran journalists, lawyers, government officials, opposition leaders, social and human rights activists pose a serious threat to their life and security which is guaranteed as the fundamental rights under the Indian Constitution. The petitioner stated before the Supreme court of India that using military grade spyware for targeted surveillance is a direct violation of fundamental right to privacy as held in K.S. Puttaswamy v. Union of India (2017). This Article deals with the set of policy questions highlighted under the purview of relationship between the privacy and security distinction that deserve further research. Also, it is an attempt to examine the interpretation of the term national security and privacy and with the help of textual and judicial interpretation.